Pengaruh Kepemimpinan, Lingkungan Kerja, dan Disiplin Kerja Terhadap Kinerja Pegawai Perumda Air Minum Tirta Moedal Kota Semarang - Wibowo, Oktovius Okky; Perdana, Tito Aditya; Purwatiningsih, Aris Puji; Ulfa, Adilla Kustya (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to test and analyze the influence of leadership, work environment, and work discipline on performance. This research uses purposive sampling, with 80 respondents as the research sample. Data collection was carried out by distributing questionnaires. Data analysis in this research was conducted using SPSS version 25. Based on the results of data processing, it was shown that the leadership and work discipline variables had a positive but not significant effect on performance, while the work environment variable had a positive and significant impact on performance.